1989
DOI: 10.1007/bf02554523
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Valtrac biofragmentable anastomosis ring with conventional suture and stapled anastomosis in colon surgery

Abstract: In a randomized, prospective study of 438 patients, the safety and efficacy of the Valtrac biofragmentable anastomotic ring (BAR) was compared with stapling and with conventional suture techniques. There was no significant difference in the morbidity, mortality, and clinical course of the patients. The BAR can effect reestablishment of intestinal continuity somewhat more rapidly, but its major advantage is its uniform applicability to all areas of the intestinal tract, except the low rectum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 15 publications
4
50
0
7
Order By: Relevance
“…141 Today the biofragmentable anastomotic ring, made of absorbable polyglycolic acid, is used most often. Four included experimental studies [107][108][109][110] showed that compression colorectal anastomosis leads to acceptable healing and strength; 6 included RCTs [111][112][113][114][115][116] provide equivalent conclusions, finding no significant differences between hand-sewn and compression colorectal anastomosis. Also, noncomparative clinical cohort studies [142][143][144][145] including up to 1360 patients have reported incidences of AL between 0.7% and 5%.…”
Section: Hand-sewn Vs Compression Colorectal Anastomosismentioning
confidence: 99%
“…141 Today the biofragmentable anastomotic ring, made of absorbable polyglycolic acid, is used most often. Four included experimental studies [107][108][109][110] showed that compression colorectal anastomosis leads to acceptable healing and strength; 6 included RCTs [111][112][113][114][115][116] provide equivalent conclusions, finding no significant differences between hand-sewn and compression colorectal anastomosis. Also, noncomparative clinical cohort studies [142][143][144][145] including up to 1360 patients have reported incidences of AL between 0.7% and 5%.…”
Section: Hand-sewn Vs Compression Colorectal Anastomosismentioning
confidence: 99%
“…Findings from other clinical studies in which a compressive anastomotic device was used for lower gastrointestinal surgery showed advantages in terms of overall operation time, postoperative complications, and recovery of bowel function, as well as anastomotic time [16,22,23]. Jejunojejunostomy in total gastrectomy for the treatment of gastric cancer is basically a small part of the entire operation.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, há registro experimental de fístulas em anastomoses colorretais com anel após irradiação 48 e fístulas em anastomoses esôfago-esofágicas por escarificação traqueal 49 . Trabalhos clínicos têm atestado segurança de utilização do anel em variadas situações clínicas e diversos sítios anatômicos 29,30,31 . Certos estudos, entretanto, apresentam índice de fístulas anastomóticas representativo em intervenções com uso do anel anastomótico biofragmentável 50 .…”
Section: Fig 4 -Face Mucosa Das Anastomoses Colocólicas Do Cão 11 Gunclassified
“…O anel de anastomose biofragmentável constituiu um dos mecanismos desenvolvidos de melhor difusão em estudos experimentais 28 e clínicos 29,30,31 . É composto de duas metades simétricas que se encaixam sob pressão, mantendo em seu mecanismo as bordas da anastomose sob compressão, com canal interno amplo; biofragmentável, decompõe-se no interior do tubo digestivo, o que facilita sua eliminação.…”
unclassified